1996
DOI: 10.1016/s0035-9203(96)90446-0
|View full text |Cite
|
Sign up to set email alerts
|

Extensive genetic diversity of Plasmodium falciparum isolates collected from patients with severe malaria in Dakar, Senegal

Abstract: While some genetic host factors are known to protect against severe Plasmodium falciparum malaria, little is known about parasite virulence factors. We have compared the genetic characteristics of P. falciparum isolates collected from 56 severe malaria patients and from 30 mild malaria patients recruited in Hôpital Principal, Dakar, Senegal. All isolates were typed using polymerase chain reaction amplification of polymorphic genetic loci (MSP-1, MSP-2, HRP1, GLURP, CSP, RESA, and the multigene family Pf60). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
130
5
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(154 citation statements)
references
References 34 publications
17
130
5
2
Order By: Relevance
“…The different allelic types of msp-1 and msp-2, as well as the different dhfr mutations, appear to be present in all the different geographic areas visited, but the sample size was too small for a more detailed analysis. However, in contrast to previous findings in endemic areas, 18,19 no association was found between severity of disease and allelic types of msp-1 block2 or msp-2.…”
Section: Discussioncontrasting
confidence: 99%
“…The different allelic types of msp-1 and msp-2, as well as the different dhfr mutations, appear to be present in all the different geographic areas visited, but the sample size was too small for a more detailed analysis. However, in contrast to previous findings in endemic areas, 18,19 no association was found between severity of disease and allelic types of msp-1 block2 or msp-2.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study reported an EIR of as low as 29 (95% CI 19-44) bites per annum (Drakeley et al, 2003). As a consequence of the lower transmission rate our study had less power than expected and even the oldest children in our study had experienced much less P. falciparum exposure than those children elsewhere in whom multiple infections appeared to be protective (Al Yaman et al, 1997a;Beck et al, 1997;Contamin et al, 1996;Farnert et al, 1999;Robert et al, 1996). The mean multiplicity in our study was lower than in most of these studies.…”
Section: Discussioncontrasting
confidence: 76%
“…Another study at the same site found that asymptomatic 3D7 family infections appeared to protect against subsequent morbidity, but FC27 family infections did not (Al Yaman et al, 1997b). In contrast, a study in Senegal failed to find any association between msp2 type and disease severity (Robert et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…Potential genotyping markers are sequences showing polymorphism within a parasite population. Polymorphisms in both repetitive sequences and unique sequences have been used for genotyping (ROBERT et al, 1996). When polymorphic repetitive sequences are amplified by PCR, a clone-specific pattern of multiple bands is seen after senaratina the PCR nroducts on a nel.…”
Section: Discussionmentioning
confidence: 99%